Dental management of patients irradiated for head and neck cancer. (4th February 2014) - Beech, N; Robinson, S; Porceddu, S; Batstone, M
Abstract Patients undergoing radiation therapy as either primary, adjuvant, combination therapy or palliative management of head and neck malignancies are prone to a range of dental complications. Strategies for prevention and management of such complications may be controversial. This article aims to highlight the current understanding and management of the dental needs for patients before, during and after radiation therapy.